2011
DOI: 10.1002/etc.716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver nanoparticles on bacterial activity in natural waters

Abstract: Silver nanoparticles (AgNPs) may be introduced into aquatic ecosystems because of their widespread use as antimicrobial agents. However, few studies have investigated the impacts of AgNPs on natural aquatic microbial activity in an environmentally relevant context. In this study, bacterioplankton were collected from nine aquatic habitats and exposed to six concentrations of carboxy-functionalized AgNP (ViveNano, 10-nm particle size, 20% Ag w/w) over 48 h. After 1 h of exposure, bacterial production and extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…This relative stimulation by TiO2NP could be based on the removal of competitors from the community; however studies investigating the effects of TiO2NP exposure on bacterial community composition are necessary to understand these mechanisms. Changes in bacterial community structure when exposed to AgNP have been previously reported (Das et al 2012, Doiron et al 2012. A reduction in abundance and number of Operational Taxonomic…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This relative stimulation by TiO2NP could be based on the removal of competitors from the community; however studies investigating the effects of TiO2NP exposure on bacterial community composition are necessary to understand these mechanisms. Changes in bacterial community structure when exposed to AgNP have been previously reported (Das et al 2012, Doiron et al 2012. A reduction in abundance and number of Operational Taxonomic…”
Section: Discussionmentioning
confidence: 80%
“…Das and co-workers observed AgNP intolerant, -recovering, -tolerant and -stimulated bacterial groups in their experiment (Das et al 2012). However, they reported a reduction in cellspecific bacterial activity after a 5-day exposure, which is in contrast to our study, showing enhanced activity rates under in situ conditions.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the EC50 values of silver ions and nanoparticles for bacterial and fungi microflora in natural water systems and in cultural liquids usually do not exceed 100-200 ppb [10,23,24]. Bactericidal concentrations of silver in water of 10-1000 ppb also are far below dangerous thresholds for humans, according to [23] in contrast with the silver PPAs with the concentrations of tens of ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Das et al [48] reported that nanosilver has significant adverse effects on growth and morphology of these filamentous green algae in a dose-dependent manner. Exposure of algal thalli to increasing concentrations of silver nanoparticles resulted in progressive depletion in algal chlorophyll content, chromosome instability and mitotic disturbance, associated with morphological malformations in algal filaments.…”
Section: Nps' Impact On Microalgaementioning
confidence: 99%